A battery cathode material precursor with a core-shell heterogeneous interface layer structure, and a preparation method and application thereof

CN122916244APending Publication Date: 2026-10-16ZHILI NEW ENERGY TECHNOLOGY (SUZHOU) CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611114588.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-27
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

目前,行业内对于多段式核壳结构前驱体的研究已较为深入,但是研究热点一般关注在前驱体内核与不同壳层间的结构及组分变化,而对于前驱体内核与相邻壳层间的界面设计,行业中鲜有研究与发掘

Benefits of technology

本发明提供的电池正极材料前驱体由内至外依次为含镍氢氧化物内核、金属氧化物异质界面层及孔隙率递增的具有多壳复合结构的壳层组成,且整体由一次纤维堆积而成。该设计通过内核与内壳层间的异质界面层实现了物理锚定与化学钝化的双重功能,有效防止核壳剥离并抑制界面副反应;同时,壳层由内至外孔隙率递增的梯度设计,使得内壳层紧实致密以保证高振实密度,外壳层疏松多孔以提供应力缓冲与离子快速传输通道,各层之间协同配合,使前驱体整体振实密度高达1.9-2.0 g/cm3,兼具高堆积密度与优异的烧结反应活性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122916244A_ABST
    Figure CN122916244A_ABST
Patent Text Reader

Abstract

The application discloses a battery positive electrode material precursor with a core-shell heterogeneous interface layer structure and a preparation method and application thereof, the battery positive electrode material precursor comprises an inner core, a heterogeneous interface layer and a shell layer arranged in sequence from inside to outside, the shell layer is a multilayer composite structure, and the porosity increases from inside to outside; the chemical general formula of the inner core and the shell layer is Ni x M (1‑x) (OH)2, and the material of the heterogeneous interface layer is a metal oxide. The battery positive electrode material precursor with the above structure has a high tap density of 1.9-2.0 g / cm 3 , and has a good solid-phase reaction melting diffusion path; the positive electrode material prepared by taking the battery positive electrode material precursor as raw material has a complete crystal form, a high tap density and a very low cation mixing effect, and the battery constructed thereby has excellent cycle stability and capacity release.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of battery technology, specifically to a battery cathode material precursor with a core-shell heterogeneous interface layer structure, its preparation method, and its application. Background Technology

[0002] With the rapid development of electrochemical energy storage technology and the continuous expansion of its market applications, batteries, with their advantages of abundant resources and low cost, have shown broad application prospects in large-scale energy storage, low-speed electric vehicles, and other fields. As a key component of batteries, the performance of cathode materials directly affects the energy density, cycle life, and safety performance of the battery. The quality of cathode materials is largely determined by their precursors; the morphology, structure, elemental distribution, and other microscopic characteristics of the precursors are inherited into the final cathode material during the subsequent sintering process. Therefore, developing high-quality cathode material precursors has become a research hotspot and a key industry focus in the battery field.

[0003] In recent years, core-shell structured cathode material precursors have attracted widespread attention due to their unique structural design advantages. By adjusting the differences in composition, structure, and morphology between the core and the outer shell, a comprehensive improvement in the electrochemical performance of cathode materials can be achieved. Currently, research on multi-segment core-shell structured precursors is relatively in-depth, but research focus is generally on the structural and compositional changes between the precursor core and different shells. However, the interface design between the precursor core and adjacent shells has received little research and exploration. Notably, patent CN121554004A emphasizes that heterogeneous interfaces should be avoided between the core and shell, arguing that the absence of heterogeneous interfaces can prevent "core-shell peeling" during cycling, thereby further improving structural stability. Summary of the Invention

[0004] Current research on core-shell structured battery cathode material precursors mainly focuses on the composition optimization and porosity control of the core and shell layers, while neglecting the design of the transition interface between the two. Furthermore, it is generally advocated to avoid heterogeneous interfaces to prevent core-shell delamination, which limits the further optimization of cathode material performance. To address this, this invention provides a battery cathode material precursor with a core-shell heterogeneous interface layer structure, its preparation method, and its application. By controlling the interface structure, the synergistic improvement of battery cycle stability and capacity can be achieved.

[0005] Specifically, the following technical solutions are provided: The first aspect of this invention provides a battery cathode material precursor with a core-shell heterogeneous interface layer structure, wherein the battery cathode material precursor has a core-shell structure and comprises, from the inside to the outside: The core, whose general chemical formula is Ni x M (1-x)(OH)2, wherein M is selected from one or more of Co, Mn, and Fe, and 0.5 ≤ x ≤ 0.98, for example 0.5, 0.6, 0.7, 0.8, 0.9, 0.92, 0.95, etc.; A heterogeneous interface layer covering at least a portion of the surface of the core, wherein the heterogeneous interface layer is made of a metal oxide. A shell covering at least a portion of the surface of the heterogeneous interface layer, the shell being a multilayer composite structure, wherein the porosity of the shell increases from the inside to the outside, and the general chemical formula of the shell is Ni. x M (1-x) (OH)2, wherein M is selected from one or more of Co, Mn, and Fe, and 0.5 ≦ x ≦ 0.98, for example 0.5, 0.6, 0.7, 0.8, 0.9, 0.92, 0.95, etc.

[0006] Furthermore, the battery cathode material precursor is formed by primary fiber stacking.

[0007] This invention provides a multi-shell core-shell structured battery cathode material precursor composed of primary fiber stacking. Its core lies in the introduction of a metal oxide heterogeneous interface layer between the core and inner shell layers. Combined with a gradient shell design featuring a compact inner shell and a loose outer shell with scattering gap patterns, it was unexpectedly discovered that, under the synergistic effect of the above structure and materials, this battery cathode material precursor not only has a high overall tap density, but also produces a cathode material with complete crystal structure, high tap density, and extremely low cation mixing effect. The constructed battery exhibits excellent cycle stability and capacity performance. This groundbreaking discovery overturns the traditional understanding that heterogeneous interfaces are harmful and provides a new design approach for interface engineering of core-shell structure precursors.

[0008] In some preferred embodiments of the present invention, the metal oxide is selected from one or more of aluminum oxide, titanium oxide, zirconium oxide, and yttrium oxide.

[0009] In some preferred embodiments of the present invention, the metal oxide accounts for 0.1wt%-0.5wt% of the mass of the battery cathode material precursor, for example, 0.2wt%, 0.3wt%, 0.4wt%, etc.

[0010] In some preferred embodiments of the present invention, the thickness of the heterogeneous interface layer is 10-200 nm, the diameter of the core is 2-6 μm, and the thickness of the shell layer is 2-8 μm.

[0011] In some preferred embodiments of the present invention, the shell layer comprises a first shell layer that is attached to the heterogeneous interface layer and a second shell layer that is away from the heterogeneous interface layer, and the porosity of the first shell layer is less than the porosity of the second shell layer.

[0012] Preferably, the porosity of the first shell layer is 5%-8%, and the porosity of the second shell layer is 8%-12%.

[0013] Preferably, the thickness of the first shell layer is 1-6 μm, and the thickness of the second shell layer is 0.5-2 μm.

[0014] In some preferred embodiments of the present invention, the tap density of the battery cathode material precursor is 1.9-2.0 g / cm³. 3 .

[0015] A second aspect of this invention provides a method for preparing a battery cathode material precursor with a core-shell heterogeneous interface layer structure as described in the first aspect, comprising the following steps: S1. Prepare mixed salt solutions, ammonia solutions, sodium hydroxide solutions, and metal oxide sols; The mixed salt solution is obtained by mixing nickel salt and M salt in a preset molar ratio; S2. The mixed salt solution, ammonia solution, and sodium hydroxide solution are continuously and concurrently fed into a container at a fixed flow rate ratio, wherein the flow rate of the mixed salt solution is V1, and the pH of the system is controlled at 11.8-12.3, to carry out a co-precipitation reaction and obtain a precursor crystal nucleus slurry. S3. The precursor crystal nucleus slurry prepared in S2 is concentrated to obtain a concentrate. After aging, a metal oxide sol is added to form a metal oxide coating layer on the surface of the precursor crystal nucleus. Then, the mixed salt solution, ammonia solution and sodium hydroxide solution are continuously and concurrently flowed into a container at a fixed flow rate ratio, wherein the flow rate of the mixed salt solution is V1, and the pH of the system is controlled at 11.2-11.5 to carry out the synthesis reaction and form a first shell layer on the surface of the metal oxide coating layer. S4. Maintaining a constant flow ratio of the mixed salt solution, ammonia solution, and sodium hydroxide solution, continuously and concurrently flow them into the container, wherein the flow rate of the mixed salt solution is increased to 4V1-6V1, and the pH of the system is controlled at 10.8-11.0, the synthesis reaction is carried out, and a second shell layer is formed on the surface of the first shell layer to obtain the precursor slurry. After aging, filtration, washing, and drying, the battery cathode material precursor is obtained.

[0016] This invention achieves the controllable construction of a core-interface-shell structure by precisely controlling the thermodynamic and kinetic conditions of the coprecipitation reaction in stages. Specifically: First, at a relatively high pH (11.8-12.3) and low supersaturation, precursor nuclei (cores) with complete crystal form and tight packing are formed at a slow growth rate; then, after concentration and aging, metal oxide sol is introduced, and a uniform oxide coating layer (heterogeneous interface layer) is formed by the adsorption of active sites on the surface of the nuclei; next, the pH is restored to a lower level (11.2-11.5) and the first shell layer is synthesized with the same slow feed rate (V1). The low supersaturation at this stage is conducive to the dense packing and slow epitaxial growth of the primary fibers, ensuring a tight bond with the heterogeneous interface layer; finally, without changing the flow rate ratio of each raw material, the feed rate of the mixed salt solution is drastically increased to 4V1-6V1, while the pH is further reduced to 10.8-11.0. The high supersaturation at this stage promotes the rapid nucleation and restricted growth of a large number of nuclei, thereby forming a loosely packed second shell layer with scattering interstitial patterns. The entire process, through the coordinated control of pH gradient reduction and feed flow rate step increase, sequentially achieves high-density core stacking, uniform coating of heterogeneous interface layer, dense growth of inner shell layer and loose construction of outer shell layer in the same system.

[0017] In some preferred embodiments of the present invention, in step S1, the concentration of the mixed salt solution is 1-2.8 mol / L, for example 2 mol / L, the concentration of the ammonia solution is 2-15 mol / L, for example 10 mol / L, and the concentration of the sodium hydroxide solution is 2-10 mol / L, for example 8 mol / L.

[0018] In some preferred embodiments of the present invention, in step S1, the concentration of the metal oxide sol is 10-200 g / L, for example 100 g / L; preferably, the metal oxide sol is prepared by alkoxide hydrolysis. Taking alumina sol as an example, the specific steps are as follows: Aluminum isopropoxide powder was added to anhydrous isopropanol and completely dissolved to obtain a transparent organic solution; Anhydrous aluminum isopropoxide organic solution was slowly added dropwise to deionized water at 70-85 °C under high-speed stirring, and hydrolysis was carried out to form a white boehmite precipitate. Add dilute nitric acid solution as a gel solvent, control the pH of the system to 3.5-4.2, and stir the system solution for 4-12 h at 70-85 ℃. The milky white suspension gradually turns into a translucent blue sol. The translucent blue sol was transferred into a distillation vessel with a vacuum of -0.06 to -0.08 MPa and heated to 60-70°C. The mixture was stirred slowly for 2-8 hours to gradually remove isopropanol, and finally alumina sol was obtained.

[0019] In some preferred embodiments of the present invention, in step S2, the container is a stirred synthesis vessel capable of automatic pH adjustment; preferably, the temperature of the coprecipitation reaction is 50-55 °C and the time is 4-10 h.

[0020] In some preferred embodiments of the present invention, in step S3, the solid content of the concentrate is 15wt%-20wt%.

[0021] In some preferred embodiments of the present invention, in step S3, the aging treatment is carried out at a temperature of 60-65 °C for 1-2 h; preferably, the aging treatment is carried out under stirring.

[0022] In some preferred embodiments of the present invention, in step S3, the volume of the metal oxide sol added is 0.5%-2% of the volume of the concentrate, and the metal oxide sol is slowly added to the concentrate for a period of 2-8 hours.

[0023] In some preferred embodiments of the present invention, the synthesis reaction in step S3 takes 24-48 hours.

[0024] In some preferred embodiments of the present invention, the synthesis reaction in step S4 takes 6-12 hours.

[0025] The third aspect of the present invention provides a cathode material, which is obtained from the battery cathode material precursor with a core-shell heterogeneous interface layer structure as described in the first aspect or the battery cathode material precursor with a core-shell heterogeneous interface layer structure prepared by the preparation method described in the second aspect.

[0026] In some preferred embodiments of the present invention, lithium hydroxide and the battery cathode material precursor are mixed uniformly at a preset molar ratio of 1.02:1, and the cathode material is obtained by sintering, crushing and sieving. The sintering process specifically involves heating to 350 °C at a heating rate of 5 °C / min and sintering for 4 h, and then heating to 730 °C at the same heating rate and sintering for 15 h.

[0027] A fourth aspect of the present invention provides a positive electrode sheet comprising the positive electrode material described in the third aspect.

[0028] In some preferred embodiments of the present invention, the positive electrode material, conductive agent carbon black (SP) and binder polyvinylidene fluoride (PVDF) are homogenized and coated in a mass ratio of 95:3:2 to obtain a positive electrode sheet.

[0029] The fifth aspect of the present invention provides a battery comprising the positive electrode sheet described in the fourth aspect.

[0030] In some preferred embodiments of the present invention, the battery can be prepared by the following method: Artificial graphite anode material, conductive agent SP, and binder PVDF are homogenized and coated in a mass ratio of 96:2:2 to obtain a negative electrode sheet; the positive electrode sheet, separator, and negative electrode sheet are stacked to obtain an electrode assembly; the electrode assembly is placed in an aluminum-plastic film and injected with conventional LiPF6 electrolyte to obtain a soft-pack battery.

[0031] The beneficial effects of this invention are: The battery cathode material precursor provided by this invention consists of a nickel hydroxide core, a metal oxide heterogeneous interface layer, and a multi-shell composite structure with increasing porosity, arranged sequentially from the inside out, and is formed by primary fiber stacking. This design achieves both physical anchoring and chemical passivation through the heterogeneous interface layer between the core and inner shell, effectively preventing core-shell separation and suppressing interfacial side reactions. Simultaneously, the gradient design of increasing porosity from the inside out ensures a compact and dense inner shell for high tap density, while the porous outer shell provides stress buffering and rapid ion transport channels. The synergistic effect of these layers results in an overall tap density of 1.9-2.0 g / cm³ for the precursor. 3 It combines high packing density with excellent sintering reactivity.

[0032] This invention utilizes a co-precipitation method to sequentially coat a heterogeneous interface layer and multiple shell layers, thereby obtaining a core-shell structured precursor product with regular structure and high batch stability. The above preparation process is simple and controllable, requiring no complex equipment or harsh conditions, making it suitable for large-scale industrial production. Furthermore, the thickness, porosity, and elemental composition of each layer can be flexibly adjusted by regulating the co-precipitation parameters, exhibiting good scalability and process adaptability.

[0033] The cathode material prepared by sintering the battery cathode material precursor provided by this invention exhibits complete crystal structure, high tap density, extremely low cation mixing effect, and gapless particle cross-section, demonstrating excellent cycle stability and capacity performance. More importantly, this invention makes a groundbreaking discovery that the appropriate introduction of a metal oxide heterostructure interface layer does not lead to core-shell separation as traditionally believed, but rather enhances the core-shell bonding force and effectively suppresses interfacial side reactions by utilizing interfacial stress. Ultimately, the constructed sodium-ion battery simultaneously possesses excellent cycle stability and high capacity performance, providing a completely new technical path for the interface engineering of core-shell structure precursors. Attached Figure Description

[0034] Figure 1 The image shows a surface electron microscope (SEM) image of the battery cathode material precursor prepared in Example 1. Figure 2 This is a cross-sectional electron microscope image of the battery cathode material precursor prepared in Example 1; Figure 3 The image shows a surface electron microscope (SEM) image of the battery cathode material precursor prepared in Comparative Example 1. Figure 4 A cross-sectional electron microscope image of the battery cathode material precursor prepared in Comparative Example 1; Figure 5 The image shows a surface electron microscope (SEM) image of the battery cathode material precursor prepared in Comparative Example 4. Figure 6 This is a cross-sectional electron microscope image of the battery cathode material precursor prepared in Comparative Example 4. Figure 7 The image shows a surface electron microscope (SEM) image of the cathode material prepared from the battery cathode material precursor obtained in Example 1. Figure 8 This is a cross-sectional electron microscope image of the cathode material prepared from the battery cathode material precursor obtained in Example 1; Figure 9 The image shows the XRD pattern of the cathode material prepared from the battery cathode material precursor obtained in Example 1. Detailed Implementation

[0035] The present invention will be further described below with reference to the accompanying drawings and specific embodiments, so that those skilled in the art can better understand and implement the present invention. However, the embodiments described are not intended to limit the present invention.

[0036] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. The terminology used herein in the specification of this invention is for the purpose of describing particular embodiments only and is not intended to be limiting of the invention. The terms “comprising” or “including” used in this invention may also be replaced with the closed form “is” or “consisting of”.

[0037] The raw materials used in the following examples are all commercially available or prepared by methods known in the art (e.g., alumina sol and titanium dioxide sol are prepared by conventional alkoxide hydrolysis). All performance tests are conducted using standardized methods to ensure data comparability and reliability. Example 1

[0038] This embodiment relates to the preparation of a battery cathode material precursor, and the specific operations are as follows: (1) Prepare 10 mol / L ammonia solution, 8 mol / L sodium hydroxide solution, 2 mol / L mixed sulfate solution (where the molar ratio of nickel, cobalt and manganese is 95:3:2, and the solvent is water), and 100 g / L alumina sol.

[0039] (2) The ammonia solution, sodium hydroxide solution and mixed salt solution prepared in step (1) are fed into a 55 ℃ constant temperature stirred synthesis vessel with a 7% mass concentration ammonia solution at a fixed flow rate ratio (the flow rate ratio of ammonia solution: sodium hydroxide solution: mixed salt solution is 1:2:4, and the initial flow rate of the mixed salt solution is 400 mL / h) for co-precipitation reaction. At the same time, the pH value of the reaction system is controlled to be 12.10 to obtain precursor crystal nucleus slurry. The feeding time is 5 h. (3) The precursor crystal nucleus slurry synthesized in step (2) was concentrated using a thickener to obtain a precursor crystal nucleus slurry with a solid content of 20 wt%. This slurry was then transferred to a 60 ℃ constant-temperature reactor with automatic pH control and stirred for aging. After aging for 2 h, 100 g / L alumina sol prepared in step (1) was slowly added to the stirred crystal nucleus slurry. The total amount added was about 1% of the total volume of the crystal nucleus slurry, and the addition time was about 4 h. After the alumina sol was added, the ammonia solution, sodium hydroxide solution and mixed salt solution prepared in step (1) were fed into the reactor in parallel at a fixed flow rate (the flow rate ratio of ammonia solution: sodium hydroxide solution: mixed salt solution was 1:2:4, and the initial flow rate of the mixed salt solution was 400 mL / h) for the synthesis reaction. At the same time, the pH value of the reaction system was controlled at 11.4, and the synthesis time was about 24 h.

[0040] (4) Maintaining a constant flow ratio of ammonia solution, sodium hydroxide solution, and mixed salt solution, the flow rate of the mixed salt solution was increased to 2000 mL / h, and the synthesis reaction continued. Simultaneously, the pH of the reaction system was controlled at 10.85, and the synthesis time was approximately 12 h, yielding the precursor slurry. The precursor slurry was then aged, filtered, washed, and dried to obtain the battery cathode material precursor Ni. 0.95 Co 0.03 Mn 0.02 (OH)2&0.0025Al2O3.

[0041] SEM images of the surface and cross-section of the battery cathode material precursor prepared in this embodiment are shown below. Figure 1 , 2 As shown in the figure, the battery cathode material precursor is formed by the stacking of primary fibers, exhibiting a multi-shell core-shell structure. There is an obvious heterogeneous interface layer structure between the core and the shell of the precursor. The inner shell is relatively compact and dense, while the outer shell is relatively loose and has scattering gap patterns. Example 2

[0042] This embodiment relates to the preparation of a battery cathode material precursor. The only difference from Example 1 is that the molar ratio of nickel, cobalt, and manganese in the mixed salt solution is 92:5:3, while all other conditions remain unchanged. The resulting battery cathode material precursor, Ni, is prepared.0.92 Co 0.05 Mn 0.03 (OH)2&0.0025Al2O3. Example 3

[0043] This embodiment relates to the preparation of a battery cathode material precursor. The only difference from Example 1 is that the molar ratio of nickel, cobalt, and manganese in the mixed salt solution is 90:6:4, while all other conditions remain unchanged. The resulting battery cathode material precursor, Ni, is prepared. 0.9 Co 0.06 Mn 0.04 (OH)2&0.0025Al2O3. Example 4

[0044] This embodiment relates to the preparation of a battery cathode material precursor. The only difference from Example 1 is that alumina sol is replaced with titanium dioxide sol, while all other conditions remain unchanged, to prepare the corresponding battery cathode material precursor Ni. 0.95 Co 0.03 Mn 0.02 (OH)2&0.005TiO2. Comparative Example 1

[0045] This comparative example relates to the preparation of a battery cathode material precursor. The only difference from Example 1 is that in step (3), a metal oxide heterostructure interface layer was not prepared. Instead, alumina sol, ammonia solution, sodium hydroxide solution, and a mixed salt solution were co-flowed into a reaction vessel to prepare a first shell layer containing alumina, as detailed below: The precursor crystal nucleus slurry synthesized in step (2) was concentrated using a thickener to obtain a precursor crystal nucleus slurry with a solid content of 20 wt%. This slurry was then transferred to a 60 ℃ constant-temperature reactor with automatic pH control and stirred for aging. After aging for 2 h, the ammonia solution, sodium hydroxide solution, and mixed salt solution prepared in step (1) were fed into the reactor in parallel at a fixed flow rate (the flow ratio of ammonia solution: sodium hydroxide solution: mixed salt solution was 1:2:4, and the initial flow rate of the mixed salt solution was 400 mL / h) for the synthesis reaction. At the same time, the alumina sol prepared in step (1) was added in parallel, with the total amount added accounting for about 1% of the total volume of the crystal nucleus slurry. The pH value of the reaction system was controlled at 11.4, and the parallel feeding time of each stream was about 24 h, thus preparing the first shell containing metal oxides.

[0046] With all other conditions remaining unchanged, the corresponding battery cathode material precursor Ni was prepared. 0.95 Co 0.03 Mn 0.02 The SEM images of the surface and cross-section of (OH)₂ and 0.0025Al₂O₃ are shown below. Figure 3 ,4 As shown, no interface layer structure was observed. Comparative Example 2

[0047] This comparative example relates to the preparation of a battery cathode material precursor. The only difference from Example 1 is that in step (3), a metal oxide heterostructure interface layer was not prepared. Instead, alumina sol, ammonia solution, sodium hydroxide solution, and a mixed salt solution were co-flowed into a reaction vessel to prepare an alumina-containing core, a first alumina-containing shell, and a second alumina-containing shell, as detailed below: (1) Prepare 10 mol / L ammonia solution, 8 mol / L sodium hydroxide solution, 2 mol / L mixed sulfate solution (where the molar ratio of nickel, cobalt and manganese is 95:3:2, and the solvent is water), and 100 g / L alumina sol.

[0048] (2) The ammonia solution, sodium hydroxide solution and mixed salt solution prepared in step (1) are fed into a 55 ℃ constant temperature stirring synthesis vessel with a 7% mass concentration ammonia solution as a constant flow rate (the flow rate ratio of ammonia solution: sodium hydroxide solution: mixed salt solution is 1:2:4, and the initial flow rate of mixed salt solution is 400 mL / h) in parallel to carry out co-precipitation reaction. At the same time, the alumina sol prepared in step (1) is added in parallel (the amount added meets the molar ratio of alumina to the total amount of metal ions in the mixed salt solution is 0.0025:1). The pH value of the reaction system is controlled to be 12.10 to obtain a precursor crystal nucleus slurry containing alumina. The feeding time is 5 h. (3) The precursor crystal nucleus slurry containing alumina synthesized in step (2) is concentrated using a thickener to obtain a precursor crystal nucleus slurry with a solid content of 20wt%. This slurry is then transferred to a 60 ℃ constant temperature reactor with automatic pH control and stirred for aging. After aging for 2 h, the ammonia solution, sodium hydroxide solution and mixed salt solution prepared in step (1) are fed into the reactor in parallel at a fixed flow rate (the flow rate ratio of ammonia solution: sodium hydroxide solution: mixed salt solution is 1:2:4, and the initial flow rate of the mixed salt solution is 400 mL / h) for the synthesis reaction. At the same time, the alumina sol prepared in step (1) is added in parallel, with the total amount added accounting for about 1% of the total volume of the crystal nucleus slurry. The pH value of the reaction system is controlled at 11.4, and the synthesis time is about 24 h.

[0049] (4) Maintaining a constant flow ratio of ammonia solution, sodium hydroxide solution, and mixed salt solution, the flow rate of the mixed salt solution was increased to 2000 mL / h, and the synthesis reaction continued. Simultaneously, the alumina sol prepared in step (1) was added in parallel (the amount added was such that the molar ratio of alumina to the total metal ions in the mixed salt solution was 0.0025:1). The pH of the reaction system was controlled at 10.85, and the synthesis time was approximately 12 h, yielding the precursor slurry. The precursor slurry was then aged, filtered, washed, and dried to obtain the battery cathode material precursor Ni. 0.95 Co 0.03 Mn 0.02 (OH)2&0.0025Al2O3. Comparative Example 3

[0050] This comparative example relates to the preparation of a battery cathode material precursor. The only difference from Example 1 is that in step (3), a metal oxide heterostructure interface layer was not prepared, while all other conditions remained unchanged, and the corresponding battery cathode material precursor Ni was obtained. 0.95 Co 0.03 Mn 0.02 (OH)2. Comparative Example 4

[0051] This comparative example relates to the preparation of a battery cathode material precursor. The only difference from Example 1 is that the preparation of the metal oxide heterostructure interface layer and the first shell layer in step (3) is omitted. All other conditions remain unchanged, and the corresponding battery cathode material precursor Ni is obtained. 0.95 Co 0.03 Mn 0.02 (OH)2, its surface and cross-section SEM images are as follows: Figure 5 , 6 As shown, the primary fiber stacking pattern inside the precursor is chaotic and disordered, lacking a core-shell structure. Application and performance testing

[0052] The battery cathode material precursors prepared in the above embodiments and comparative examples were used to prepare cathode materials and assembled into pouch cells for testing of electrical performance.

[0053] Preparation of cathode material: Lithium hydroxide and cathode material precursor were mixed evenly at a molar ratio of 1.02:1 and then transferred into a sintering furnace for heat treatment. The mixture was heated to 350 °C at a heating rate of 5 °C / min and sintered for 4 h. Then, it was heated to 730 °C at the same heating rate and sintered for 15 h. Finally, it was cooled to room temperature, crushed and sieved to obtain cathode material for later use.

[0054] Battery fabrication: A positive electrode sheet is prepared by homogenizing and coating a positive electrode material, conductive agent carbon black (SP), and binder polyvinylidene fluoride (PVDF) in a mass ratio of 95:3:2. A negative electrode sheet is prepared by homogenizing and coating an artificial graphite negative electrode material, conductive agent SP, and binder PVDF in a mass ratio of 96:2:2. The positive electrode sheet, separator, and negative electrode sheet are stacked to obtain an electrode assembly. The electrode assembly is placed in an aluminum-plastic film and injected with conventional LiPF6 electrolyte to obtain a pouch battery.

[0055] Tap density test: The tap density of each battery cathode material precursor prepared in the above examples and comparative examples was tested using a tap density tester; First discharge specific capacity test: The first discharge specific capacity of the soft-pack batteries assembled from the positive electrode materials prepared from the positive electrode material precursors prepared in the above examples and comparative examples was tested using a Xinwei battery tester. The test voltage was 2.85 V-4.25 V, the temperature was 25 ℃, and the first charge and discharge rate was 0.1 C.

[0056] Charge-discharge cycle performance test: The charge-discharge cycle performance of the pouch batteries assembled from the positive electrode materials prepared from the positive electrode material precursors prepared in the above examples and comparative examples was tested using a Xinwei battery tester. The test voltage was 2.85V-4.25V, the temperature was 25℃, the charge-discharge rate was 1C, and the charge-discharge cycle was 1000 cycles.

[0057] The test results are summarized in Table 1 below:

[0058] Table 1

[0059] From Table 1 and Figure 8 , 9 It can be seen that the battery cathode material precursors prepared in Examples 1-4 have high tap density, and the cathode material obtained by sintering has complete crystal structure and high tap density. The soft-pack battery constructed from it exhibits high capacity performance and excellent cycle stability.

[0060] As can be seen from Example 1 and Comparative Examples 1-3, although the battery cathode material precursors with core-shell structure but no heterogeneous interface layer (Comparative Examples 1-3) have higher tap density, their capacity utilization and cycle stability are significantly lower than those of Example 1. In addition, the battery cathode material precursors without heterogeneous interface layer and core-shell structure prepared in Comparative Example 4 have a disordered and chaotic internal primary fiber stacking mode, resulting in a lower tap density and the worst capacity utilization and cycle stability.

[0061] The embodiments described above are merely some examples listed to fully illustrate the present invention, and the scope of protection of the present invention is not limited thereto. The technical features of the above embodiments can be combined arbitrarily. For the sake of brevity, not all possible combinations of the technical features in the above embodiments are described. However, as long as the combination of these technical features does not contradict each other, it should be considered within the scope of this specification. Equivalent substitutions or modifications made by those skilled in the art based on the present invention are all within the scope of protection of the present invention. The scope of protection of the present invention is determined by the claims.

Claims

1. A battery cathode material precursor with a core-shell heterogeneous interface layer structure, characterized in that, The battery cathode material precursor has a core-shell structure, comprising, from the inside out: The core, whose general chemical formula is Ni x M (1-x) (OH)2, wherein M is selected from one or more of Co, Mn, and Fe, and 0.5 ≤ x ≤ 0.98; A heterogeneous interface layer covering at least a portion of the surface of the core, wherein the heterogeneous interface layer is made of a metal oxide. A shell covering at least a portion of the surface of the heterogeneous interface layer, the shell being a multilayer composite structure, wherein the porosity of the shell increases from the inside to the outside, and the general chemical formula of the shell is Ni. x M (1-x) (OH)2, wherein M is selected from one or more of Co, Mn, and Fe, and 0.5≦x≦0.

98.

2. The battery cathode material precursor with a core-shell heterogeneous interface layer structure according to claim 1, characterized in that, It must contain at least one of the following characteristics: The metal oxide is selected from one or more of aluminum oxide, titanium oxide, zirconium oxide, and yttrium oxide; The metal oxide accounts for 0.1wt%-0.5wt% of the mass percentage of the battery cathode material precursor. The thickness of the heterogeneous interface layer is 10-200 nm; The diameter of the core is 2-6 μm; The thickness of the shell is 2-8 μm.

3. The battery cathode material precursor with a core-shell heterogeneous interface layer structure according to claim 1, characterized in that, The shell layer comprises a first shell layer that is attached to the heterogeneous interface layer and a second shell layer that is away from the heterogeneous interface layer, and the porosity of the first shell layer is less than the porosity of the second shell layer. And / or, the tap density of the battery cathode material precursor is 1.9-2.0 g / cm³. 3 .

4. The battery cathode material precursor with a core-shell heterogeneous interface layer structure according to claim 3, characterized in that, The porosity of the first shell layer is 5%-8%, and the porosity of the second shell layer is 8%-12%. And / or, the thickness of the first shell is 1-6 μm, and the thickness of the second shell is 0.5-2 μm.

5. A method for preparing a battery cathode material precursor with a core-shell heterogeneous interface layer structure as described in any one of claims 1-4, characterized in that, Includes the following steps: S1. Prepare mixed salt solutions, ammonia solutions, sodium hydroxide solutions, and metal oxide sols; The mixed salt solution is obtained by mixing nickel salt and M salt in a preset molar ratio; S2. The mixed salt solution, ammonia solution, and sodium hydroxide solution are continuously and concurrently fed into a container at a fixed flow rate ratio, wherein the flow rate of the mixed salt solution is V1, and the pH of the system is controlled at 11.8-12.3, to carry out a co-precipitation reaction and obtain a precursor crystal nucleus slurry. S3. The precursor crystal nucleus slurry prepared in S2 is concentrated to obtain a concentrate. After aging, a metal oxide sol is added to form a metal oxide coating layer on the surface of the precursor crystal nucleus. Then, the mixed salt solution, ammonia solution and sodium hydroxide solution are continuously and concurrently flowed into a container at a fixed flow rate ratio, wherein the flow rate of the mixed salt solution is V1, and the pH of the system is controlled at 11.2-11.5 to carry out the synthesis reaction and form a first shell layer on the surface of the metal oxide coating layer. S4. Maintaining a constant flow ratio of the mixed salt solution, ammonia solution, and sodium hydroxide solution, continuously and concurrently flow them into the container, wherein the flow rate of the mixed salt solution is increased to 4V1-6V1, and the pH of the system is controlled at 10.8-11.0, the synthesis reaction is carried out, and a second shell layer is formed on the surface of the first shell layer to obtain the precursor slurry. After aging, filtration, washing, and drying, the battery cathode material precursor is obtained.

6. The preparation method according to claim 5, characterized in that, In step S1, the concentration of the mixed salt solution is 1-2.8 mol / L; And / or, the concentration of the ammonia solution is 2-15 mol / L; And / or, the concentration of the sodium hydroxide solution is 2-10 mol / L; And / or, the concentration of the metal oxide sol is 10-200 g / L; And / or, the metal oxide sol is prepared by alkoxide hydrolysis.

7. The preparation method according to claim 5, characterized in that, In step S2, the temperature of the coprecipitation reaction is 50-55 °C, and the time is 4-10 h; In step S3, the aging treatment is carried out at a temperature of 60-65 ℃ for 1-2 h. In step S3, the solid content of the concentrate is 15wt%-20wt%; In step S3, the volume of the added metal oxide sol is 0.5%-2% of the volume of the concentrate; In step S3, the metal oxide sol is slowly added to the concentrate over a period of 2-8 hours. In step S3, the synthesis reaction takes 24-48 hours. In step S4, the synthesis reaction takes 6-12 hours.

8. A positive electrode material, characterized in that, The battery cathode material precursor with a core-shell heterogeneous interface layer structure as described in any one of claims 1-4 or prepared by the preparation method described in any one of claims 5-7 is obtained.

9. A positive electrode sheet, characterized in that, It includes the cathode material as described in claim 8.

10. A battery, characterized in that, It includes the positive electrode sheet as described in claim 9.

Citation Information

Patent Citations

  • Inside-dense and outside-loose type small-particle-size high-nickel ternary positive electrode material precursor, preparation method thereof, high-nickel ternary positive electrode material and lithium ion battery

    CN121554004A